Kinetic and kinematic characteristics change with systematic variation of pole length in cross-country skiing - Smith, G.; Nilsson, J.; Jakobsen, V.; Tveit, P. (2002)
Double poling performance depends in large part on the propulsive force component which in turn depends on resultant force and pole angle. Pole length affects each of these characteristics with a clear advantage for longer poles during poling phase. However, a full motion cycle also includes a recovery phase in which the poles are swung forward which was not evaluated in this study. The recovery phase duration and therefore the cycle time may also be affected by pole length. The two phases together will determine average propulsive force over the whole cycle and ultimately determine the mean skiing speed of the cycle. While longer poles are advantageous for achieving a larger propulsive force impulse in maximal double poling, further study will be required to determine the influences on poling cycle rate, metabolic cost and other ski techniques that also affect race performance. Follow-up to this study will require a more comprehensive assessment involving both metabolic and mechanical measures.